Assessing the JEOL CRYO ARM 300 for high-throughput automated single-particle cryo-EM in a multiuser environment. (2020) - Fislage, Marcus; Shkumatov, Alexander V.; Stroobants, Annelore; Efremov, Rouslan G.
No abstract available